2017
DOI: 10.1016/j.jhealeco.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Health care demand elasticities by type of service

Abstract: We estimate within-year price elasticities of demand for detailed health care services using an instrumental variable strategy, in which individual monthly cost shares are instrumented by employer-year-plan-month average cost shares. A specification using backward myopic prices gives more plausible and stable results than using forward myopic prices. Using 171 million person-months spanning 73 employers from 2008–2014, we estimate that the overall demand elasticity by backward myopic consumers is −0.44, with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 18 publications
1
49
4
1
Order By: Relevance
“…Not surprisingly, our results are quite similar to those of Courtemanche et al (2017a). We find that the ACA increased health insurance coverage by 5 percentage points in states that expanded Medicaid and 9 Also see Ellis, Martins and Zhu (2017). Using data on 171 million person-months from MarketScan, the authors found a price elasticity of demand for ambulance services of -1 among "forward-looking" individuals, suggesting that extending insurance coverage under the ACA would increase utilization of ambulance services.…”
Section: Introductionsupporting
confidence: 77%
“…Not surprisingly, our results are quite similar to those of Courtemanche et al (2017a). We find that the ACA increased health insurance coverage by 5 percentage points in states that expanded Medicaid and 9 Also see Ellis, Martins and Zhu (2017). Using data on 171 million person-months from MarketScan, the authors found a price elasticity of demand for ambulance services of -1 among "forward-looking" individuals, suggesting that extending insurance coverage under the ACA would increase utilization of ambulance services.…”
Section: Introductionsupporting
confidence: 77%
“…The finding that consumers are not price-sensitive, conditional on insurance enrollment, is in contrast to what has been found for medical care (see, for example, Ellis, Martins, & Zhu, 2017;Meyerhoefer & Zuvekas, 2010). Nonetheless, MZM note that even older studies of dental care demand found that consumers were not price-sensitive over a broad range of out-of-pocket costs.…”
Section: Discussionmentioning
confidence: 76%
“…The price elasticities of demand for MERS was consistent with those of previously reported pharmacist's services. Overall, the demand for healthcare services is price inelastic 30,31 . However, preventive care and drug-related services appear to be less sensitive to price changes compared to other health care services 32 .…”
Section: Discussionmentioning
confidence: 99%